Cubik system: maximizing possibilities of in-house computer-guided surgery for complex craniofacial reconstruction. Issue 12 (December 2021) - Tel, A.; Tuniz, F.; Sembronio, S.; Costa, F.; Bresadola, V.; Robiony, M.
Abstract: Craniofacial reconstruction represents a major challenge due to the complex anatomical morphology. Although implant production has often been outsourced to external companies, in-house planning and manufacturing has developed in many centres. This note introduces a conceptualized modular mould system to perform any desired craniofacial reconstruction, named 'Cubik', inspired by the famous Rubik's cube. A sophisticated virtual process is described that simulates realistic cranio-orbital resections, and the workflow to create multi-component moulds in order to achieve intraoperatively moulded implants is presented. The description focuses on the appropriate definition of interfaces between the subdivision surfaces of the planned implant, which is the key element to successful design and function of the moulds during surgery and is the peculiarity of the Cubik system. The use of Cubik does not prolong the overall duration of surgery, and it appears to be a very versatile tool, allowing personalized implants with different morphology to be created, which are suitable to cover every potential defect of the skull and the orbital region. This study extends the potential of in-house production, allowing highly accurate implantable craniofacial implants to be fabricated, and in the future this might represent a solution to achieve in-house replacement of other segments of the facial skeleton.